2019
DOI: 10.1556/168.2019.20.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental harvest in a tropical seagrass meadow leads to shift in associated benthic communities

Abstract: Seagrass meadows represent key ecosystems in coastal areas worldwide, hosting a great biodiversity of associated communities and thereby providing a large range of ecosystem services. In this study we present an experimental approach to investigate the effects of seagrass losses on related macrofauna assemblages. Over a three year period, seagrass canopies were removed in experimental plots and changes in epifauna, infauna and respective functional groups were recorded. The experimental removal of seagrass lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…It has been hypothesized that significant changes to seagrass faunal communities may influence seagrass sediment carbon stocks, in particular bioturbators [11,12]. Burrowing shrimp of Gazi Bay, assumed to be part of the Callianassidae family, have an important bioturbation capacity, with a sediment turnover here estimated here to be around 948 ± 342 (SE)g.d -1 DW.…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 81%
See 2 more Smart Citations
“…It has been hypothesized that significant changes to seagrass faunal communities may influence seagrass sediment carbon stocks, in particular bioturbators [11,12]. Burrowing shrimp of Gazi Bay, assumed to be part of the Callianassidae family, have an important bioturbation capacity, with a sediment turnover here estimated here to be around 948 ± 342 (SE)g.d -1 DW.…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 81%
“…Seagrass loss can also lead to alterations in faunal communities with a shift toward a domination of bioturbator organisms, therefore accelerating the remineralisation of Corg [11,12]. In the sub-tropical and tropical regions of the world, the main macrofaunal bioturbators are Callianassidae shrimps (Decapoda : Axiidea) [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an unstable sediment surface is likely to be uninhabitable for many currently existing benthic species within natural tropical bays, such as calcifying algae, urchins and juvenile lobster (Lozano-Álvarez et al, 2009). The benthic community has been shown to be tightly linked to the presence or absence of seagrass (Lundquist et al, 2018;Seitz and Ewers Lewis, 2018;Cadier and Frouws, 2019;Githaiga et al, 2019). Once seagrass is lost, the community assemblage often shifts toward bioturbating organisms that can further hinder seagrass reestablishment (Cadier and Frouws, 2019).…”
Section: Loss Of Ecosystem Services Exacerbates Negative Climate Chan...mentioning
confidence: 99%
“…The loss of foundation species may increase the vulnerability of communities by triggering a sequence of extinctions (Berg et al 2015). Cadier and Frouws (2019) demonstrated that the removal of seagrass in Gazi Bay (Kenya) has negative impacts on associated benthic species that depended on this primary producer as habitat. The seagrass modifies the characteristics of the ecosystem by creating 3D structures above and below ground, increasing oxygenation of the sediment, increasing the trap of sediment and consequently carbon sequestration.…”
Section: Contributions To the Present Selection Of Manuscriptsmentioning
confidence: 99%